Reviving the American dream : the economy, the states & the federal government - Rivlin, Alice M. (Brookings Institution, 1992)
The American dream is fading: for nearly two decades, the economy has been performing below par, the quality of life has deteriorated, and the government has not confronted the public problems that concern citizens most. In this provocative book, Alice Rivlin offers a straightforward, nontechnical look at the issues threatening the American dream and proposes a solution: restructure responsibilities between the federal and state government. Under her plan, the federal government would eliminate most of its programs in education, housing, highways, social services, economic development, and job.